2007
DOI: 10.1097/01.tp.0000288807.52520.5e
|View full text |Cite
|
Sign up to set email alerts
|

C4d-Positive Chronic Rejection: A Frequent Entity With a Poor Outcome

Abstract: These data indicate that C4d positive chronic rejection is very common, associated with proteinuria, and has a poor outcome. A larger study is warranted to identify which immunosuppressive regimen may modify the poor course of this entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 18 publications
1
18
0
9
Order By: Relevance
“…We found that in this unique cohort of renal allograft recipients Ն10 yr after transplantation, identified on review of our pathology database, 25% were C4d ϩ , which is similar to the prevalence of C4d positivity in allograft biopsies performed at earlier times. 21,28 Diffuse positive C4d staining (C4d3 Ͼ50%) as defined by Banff 2007 27 was seen in 23 patients; two patients had focal PTC C4d staining (C4d2 10 to 50%) in their index biopsies. Evaluation of historical samples, retrospectively stained for C4d, revealed that the great majority of pervious biopsies from C4d ϩ patients were also positive.…”
Section: Discussionmentioning
confidence: 99%
“…We found that in this unique cohort of renal allograft recipients Ն10 yr after transplantation, identified on review of our pathology database, 25% were C4d ϩ , which is similar to the prevalence of C4d positivity in allograft biopsies performed at earlier times. 21,28 Diffuse positive C4d staining (C4d3 Ͼ50%) as defined by Banff 2007 27 was seen in 23 patients; two patients had focal PTC C4d staining (C4d2 10 to 50%) in their index biopsies. Evaluation of historical samples, retrospectively stained for C4d, revealed that the great majority of pervious biopsies from C4d ϩ patients were also positive.…”
Section: Discussionmentioning
confidence: 99%
“…and function, some did not confirm this association (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (20,(20)(21)(22)(23)(24) …”
Section: C4d−/dsa+ (N = 39 149%) C4d+/dsa− (N = 49 187%) and C4dmentioning
confidence: 99%
“…That might be explained by the different sensitivity of C4d detection methods and also by the dynamic nature of the rejection, in which course C4d expression may appear and disappear over the time depending on the activity of the process. Beyond that, there are some findings confirming the enhancing role of other mechanisms of DSA-driven endothelial damage in late chronic rejection, which are not directly associated with complement activation [36,37]. However in general the literature data concerning this issue are controversial -while some authors describe important influence of C4d-positivity on chronic rejection prognosis [26,38], the others indicate that prognosis for C4d-posistive chronic rejection does not differ from such for C4d-negative or even is better [17,39].…”
Section: Discussionmentioning
confidence: 75%